Weak corporate investment requires immediate action - Marcel Fratzscher; Martin Gornig; Alexander Schiersch (DIW Economic Bulletin, 2016)
Although the federal government has been taking steps to strengthen investment in Germany, it remains considerably low. This includes private investment, on which thepresent study focuses. German companies are barely investing more than they did before the crisis, but this is not the case elsewhere: in the US, for example, the level of investment is nearly 14 percent higher than it was in 2007. One year ago, the Experts Commission "Strengthening Investment in Germany," presented a plan comprising concrete recommendations for mitigating or even eliminating Germany's investment weakness. The report contained proposals for increasing public investment, as well as measures for strengthening private investment. Since then, however, far too little progress has been made in the four primary fields of action for private investment identified by the Experts Commission (digital networks, energy infrastructure, innovations, and young enterprises). The need for action remains high; among other measures, tax incentives for investment could help.
Keywords: E22; E61; H54; 330; investment; private sector; expert commission; capital stock